Empirical Research on the Effect of Oil Revenues on Government Debt in The Case of Azerbaijan - Huseynli, Nigar (International Journal of Energy Economics and Policy, 2025)
Oil is one of the leading natural resources used to increase the welfare of countries. Especially in Azerbaijan, which is an oil-based country, the importance of oil in the revenues provided to the state treasury cannot be denied. As a matter of fact, these revenues are important within the amount of foreign debt acquired for capital development. Borrowing is one of the financing tools that governments frequently use for various reasons and purposes. Revenues obtained from two main channels are used for the state to fulfill its responsibilities and investments. The aim of this study is to investigate the effect of oil revenues on government debt in Azerbaijan. Annual data between 2000 and 2020 used in the research were obtained from the World Bank. In the study carried out within the framework of a bivariate model, logarithmic values of the variables were included in the analysis. As a result of the empirical research, it was determined that there was no strong and significant relationship between the two variables. This may be because the country is still dependent on oil, its non-oil sectors are not sufficiently developed, and as a result, its non-oil revenues are very low.